Smart Street Lighting System - Yahya, Muhammad Hasif; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2021)
Nowadays, the populations of humankind are getting bigger every year. The increasing population has leads to the higher demand of electrical energy to fulfil users daily life. In Malaysia, the main resource in generating electrical energy was by converting non-renewable energy instead of renewable energy.  Non- renewable energy has been used because it can produce a bigger output of electrical energy. However, this type of energy is expected to run out within a century. Thus, the usage of electrical energy must be efficient. Smart Street Lighting System (SSLS) has been proposed to replace the current street lights. SSLS is made up of two sensors which are PIR Sensor and Light Dependent Resistor (LDR). PIR Sensor used to detect the presence of vehicle while LDR is used to sense surrounding light intensity. Both sensors will determine either to open or closed the SSLS circuit. The circuit is closed when two conditions are met. The conditions are there is low intensity of surrounding light and there is a presence of vehicle detected by PIR Sensor. SSLS circuit is in open circuit when there are no demands, hence it controlled the usage of electrical energy efficiently.  The result of this project has shown a lower value of kilowatt-hour which is up to a 44% decrease in power consumption.